Resolution of Type 2 Diabetes Following Bariatric Surgery: Implications for Adults and Adolescents - Nandagopal, Radha (Mary Ann Liebert, Inc., 2010)
Bariatric surgery is now widely reported to ameliorate or resolve type 2 diabetes mellitus in adults. Some clinical investigators even suggest its use as an early therapeutic intervention for type 2 diabetes in patients not meeting standard criteria for bariatric surgery. However, little is known about the exact mechanisms explaining the metabolic consequences, and much active investigation is underway to identify hormonal changes leading to diabetes resolution. This review includes a detailed description of various bariatric surgical procedures, including the latest less-invasive techniques, and a summary of current data providing insight into the short- and long-term metabolic effects. We outline current hypotheses regarding the mechanisms by which these surgical procedures affect diabetes and report on morbidity and mortality. Finally, we discuss the available data on bariatric surgery in adolescent patients, including special considerations in this potentially vulnerable population.